Examination Of The Role Of An AC Storage System In Microgrid Frequency And Voltage Control - Dandan Zhao (Journal of Applied Science and Engineering, 2025)
This article explores the role of an AC storage system in microgrid frequency and voltage control. The studied microgrid is part of a medium voltage radial distribution network and comprises two types of distributed generation units: gas units and photovoltaic units. Depending on the type of production units within the microgrid, an AC storage system has been employed to modify the dynamic behaviour of the microgrid by implementing a primary frequency and voltage control scheme. This approach aims to fulfil the requirements of sensitive loads within the microgrid. Two distinct scenarios, involving unplanned islanding and intentional islanding, have been considered to assess the microgrid's response to disturbances. Ultimately, the dynamic performance of the microgrid has been compared with a scenario in which the microgrid lacks an AC storage system. Simulation results indicate that the AC storage system, along with its control scheme, effectively meets the criteria for sensitive loads.